Trading and Human Rights in Non-Self-Governing Territories - Jiménez-Sánchez, Carolina (My University, 2020)
The relation between European Union and Human Rights Law has not always been close. The global projection of the EU, and its interest in becoming a leader in international trade and economic stability is facing its negative impact in some territories, specially those affected by human rights violation or negation of fundamental rules of International Law, such as ius cogens self-determination of people. This paper will examine whether the practice of the European Union trading with occupying and administrative powers in some territories (Crimea, Palestine, Western Sahara, Kosovo or Gibraltar) could jeopardise its compliance with its own values and principles.
Keywords: Derechos humanos; Non-Self_Governing Territories; EU; Human Rights